Fibroids that do not distort the uterine cavity and IVF success rates: an observational study using extensive matching criteria. (5th December 2016) - Christopoulos, G; Vlismas, A; Salim, R; Islam, R; Trew, G; Lavery, S
Abstract : Objective: To assess the impact of non‐cavity‐distorting fibroids on in vitro fertilisation (IVF) pregnancy outcomes. Design: A retrospective, matched, single‐centre, cohort study was performed. Setting: The IVF unit of a tertiary, university hospital. Population: We analysed all women with non‐cavity‐distorting uterine fibroids undergoing IVF/intracytoplasmic sperm injection (ICSI) cycles from 1 January 2011 to 1 May 2015. Methods: Each woman was matched with two separate controls of the same age (±6 months), stimulation protocol (gonadotropin‐releasing hormone agonist or antagonist), starting dose of follicle‐stimulating hormone (FSH), number of embryos transferred (one or two), day of transfer (day 3 or day 5), and no uterine fibroids identified by transvaginal ultrasound. Main outcome measures: Clinical pregnancy and live birth rates. Results: Our study demonstrates that the presence of non‐cavity‐distorting fibroids appears to negatively affect clinical pregnancy (odds ratio, OR 0.62; 95% confidence interval, 95% CI 0.41–0.94) and live birth rates (OR 0.58; 95% CI 0.48–0.78) in patients undergoing their first IVF/ICSI cycle, when matched with controls of the same age, starting dose of FSH, stimulation protocol, number of embryos, and day of embryo transfer. The deleterious effect of fibroids on live birth rates was significant in women with two or more fibroids (OR 0.47; 95% CI 0.26–0.83) and in women with fibroids of ≥30 mm in diameter (OR 0.41; 95% CI 0.19–0.89). The negative impact of non‐cavity‐distorting fibroids was also present in women with an embryo transfer on day 5 (OR 0.58; 95% CI 0.35–0.94). Conversely, in women with single fibroids of <30 mm in diameter, no difference in pregnancy outcomes was identified. Conclusions: A well‐designed, adequately powered, randomised controlled trial is required to address the role of medical or surgical interventions in patients with intramural and subserosal fibroids before undergoing fertility treatment. Tweetable abstract: Non‐cavity‐distorting fibroids negatively affect pregnancy rates after IVF. Tweetable abstract: Non‐cavity‐distorting fibroids negatively affect pregnancy rates after IVF.